2011
DOI: 10.1007/s11121-011-0238-1
|View full text |Cite
|
Sign up to set email alerts
|

Philani Plus (+): A Mentor Mother Community Health Worker Home Visiting Program to Improve Maternal and Infants’ Outcomes

Abstract: Pregnant mothers in South African townships face multiple health risks for themselves and their babies. Existing clinic-based services face barriers to access, utilization, and human resource capacities. Home visiting by community health workers (CHW) can mitigate such barriers. The Philani Plus (+) Intervention Program builds upon the original Philani CHW home-visiting intervention program for maternal and child nutrition by integrating content and activities to address HIV, alcohol, and mental health. Pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
159
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 56 publications
2
159
1
3
Order By: Relevance
“…l 37 trials reporting a universal preventive intervention 61,123,129,146,147,150,[153][154][155][156][157][180][181][182][183][184][185][186][187][197][198][199][200][207][208][209][210][211][212][217][218][219][220][225][226][227][228] l 20 trials reporting a selective preventive intervention 149,[158][159][160][161][162][163][188][189][190][191][192][201]…”
Section: Level Of Preventive Interventionmentioning
confidence: 99%
“…l 37 trials reporting a universal preventive intervention 61,123,129,146,147,150,[153][154][155][156][157][180][181][182][183][184][185][186][187][197][198][199][200][207][208][209][210][211][212][217][218][219][220][225][226][227][228] l 20 trials reporting a selective preventive intervention 149,[158][159][160][161][162][163][188][189][190][191][192][201]…”
Section: Level Of Preventive Interventionmentioning
confidence: 99%
“…The difference in means (MD) and respective 95%CI were used to measure the absolute difference between the means in interventions and comparison groups. Since one included study was a cluster randomized trial, we used values of the intra-class correlation coefficient reported in a previous publication related to this intervention 34 to adjust trial analysis for clustering and enter its adjusted values in the meta-analysis. Consistent condom use (dichotomous outcome) was estimated using intention-to-treat analysis and included all subjects who were randomized, regardless of baseline condom use behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Research shows that interventions beyond the clinic, utilizing mobile MHWs can become expensive. But, with efficiently deployed technologies and well-trained MHWs, home visit interventions can be beneficial and cost effective [7,24]. Mishandled deployment and narrow capabilities of MHWs can cause increases in costs of home visits up to twice that of clinical visits [7].…”
Section: Cost Effectivenessmentioning
confidence: 99%